2020
DOI: 10.3389/fphar.2020.603476
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sophora flavescens (Kushen) Based Traditional Chinese Medicine in the Treatment of Ulcerative Colitis: Clinical Evidence and Potential Mechanisms

Abstract: Background: Radix Sophorae flavescentis (Kushen), a Chinese herb, is widely used in the treatment of ulcerative colitis (UC) with damp-heat accumulation syndrome (DHAS) according to traditional Chinese medicine (TCM) theory.Objective: The aim of this study was to illuminate the clinical efficacy and potential mechanisms of Kushen-based TCM formulations in the treatment of UC with DHAS.Materials and Methods: A systematic literature search was performed in the PubMed, EMBASE, Chinese Biomedical Literature databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Our results suggested that phaseolin (1) reduced NO synthesis and iNOS expression, (2) suppressed pro-inflammatory mediators and increased anti-inflammatory mediators, (3) inhibited cell-to-ECM adhesion through Ninj1 downregulation, (4) reduced cell migration, and MMP expression, and (5) reduced nuclear NF-κB translocation. The inhibitory effect of phaseolin on IL-6 expression was consistent with Chen’s expectations through a network pharmacology analysis [ 6 ].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our results suggested that phaseolin (1) reduced NO synthesis and iNOS expression, (2) suppressed pro-inflammatory mediators and increased anti-inflammatory mediators, (3) inhibited cell-to-ECM adhesion through Ninj1 downregulation, (4) reduced cell migration, and MMP expression, and (5) reduced nuclear NF-κB translocation. The inhibitory effect of phaseolin on IL-6 expression was consistent with Chen’s expectations through a network pharmacology analysis [ 6 ].…”
Section: Discussionsupporting
confidence: 81%
“…Recently, it has been reported that Kushen (Radix Sophorae flavescentis ), which is a promising herbal medicine against inflammation, contains phaseolin as one of the bioactive ingredients [ 36 ]. In addition, Chen et al predicted that phaseolin is as a major bioactive ingredient responsible for the anti-inflammatory activity represented by Kushen based on a component–target–pathway network [ 6 ]. However, the mechanisms underlying the anti-inflammatory effects of Kushen and the biological relevance of its component phaseolin against inflammation are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kuraninone is a natural flavonone purified from Sophora flavescens Aiton, one of the traditional Chinese medicinal herbs. Sophora flavescens is known to have anti-inflammatory effects [ 20 ] and is used to treat inflammatory diseases such as ulcerative colitis [ 21 ], Behcet syndrome [ 22 ], arthritis [ 23 ], pulmonary fibrosis [ 24 ], asthma [ 25 ], and influenza infection [ 24 ]. Other studies have also reported anti-inflammatory effects of kuraninone through its potent inhibition of cyclooxygenase (COX)-1 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%